Foliar Resorption of Some Macro-(N, P, S) and Micronutrients (Fe, Zn, Cu, Mn) in Pterocarya Fraxinifolia (Poiret) Spach Forests in Turkey - Huseyinoglu, Rena; Kutbay, Hamdi Guray; Ok, Tolga; Yalcin, Erkan; Bilgin, Ali; Horuz, Ayhan (Society National Protection Nature Acclimatization France, 2016)
Pterocarya fraxinifolia (Poiret) spach has a rather restricted distribution in Turkey and occurs in swamp forests. Foliar resorption of some macro- (N, P and S) and micronutrients (Fe, Mn, Zn, Cu) in northern and southern populations of P. fraxinifolia in Turkey was studied. In northern populations, comparatively to southern populations, nitrogen resorption efficiency (NRE) was higher, while phosphorus resorption efficieny (PRE) was lower. Both northern and southern populations were P-proficient, while only northern populations were N-proficient. Negative RE values were found with respect to Zn and MnRE in southern populations. SRE was found to be higher as compared to other deciduous species. It has been found that NRE/PRE ratios >1 in northern populations, while <1 in southern populations.